DINAMIKA AIR DAN NUTRISI PADA MEDIA PEMBIBITAN KENTANG DENGAN TEKNIK FERTIGASI KAPILER - Utari, Hirdilla Safitri Dwi; Wijaya, Krissandi; Sudarmaji, Arief; Kuncoro, Purwoko Hari; Mustofa, Asna; Irawadi, Irawadi (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2024)
The application of hydroponics or aeroponics, by which the water and nutrients (fertigation) can be supplied precisely and automatically, in potato-seedling can produce good quality seed-tubers, but generally requires high investment-costs. Alternatively, evapotranspirative-wick-based capillary-fertigation offers an efficient fertigation-technique, but tends to be less-utilized, thus needs to be optimized. This research focused on the application of the evapotranspirative-wick-based capillary-fertigation-technique for potato-seedlings with various seedling-media-types and organic-fertilizer-doses as well as identifying the water- and nutrients-dynamics in the media. Totally 36 media-polybags, including 12 treatment-combinations (4 media-types: cocopeat-soil, raw husk-soil, burnt husk-soil, whole soil with 3 organic-fertilizer-doses: 20, 30, 40 kg/ha) under 3 replications were prepared. Each polybag was equipped with 5 evapotranspirative-wicks, planted with G1 seed-tubers, placed inside a fertigation-tube, and covered. The parameter of water- (θ, Ks, ∆S) and nutrients-dynamics (available-N, available-P) in each polybag were measured periodically, and micro-climates were observed daily. The water- and nutrients-dynamics in the media fluctuated throughout the seedling period. Optimal water-dynamics parameters occured in the whole soil with 30 ton/ha organic-fertilizer. Optimal nutrients-dynamics parameters were found in the cocopeat-soil with 40 kg/ha organic-fertilizer, to which the highest weight of G2 seed-tubers could be produced.